Lung protection by inhalation of exogenous solubilized extracellular matrix. - Jinglei Wu; Priya Ravikumar; Kytai T Nguyen; Connie C W Hsia; Yi Hong (PLoS ONE)
Decellularized extracellular matrix (ECM) contains complex tissue-specific components that work in concert to promote tissue repair and constructive remodeling and has been used experimentally and clinically to accelerate epithelial wound repair, leading us to hypothesize that lung-derived ECM could mitigate acute lung injury. To explore the therapeutic potential of ECM for noninvasive delivery to the lung, we decellularized and solubilized porcine lung ECM, then characterized the composition, concentration, particle size and stability of the preparation. The ECM preparation at 3.2 mg/mL with average particle size <3 μm was tested in vitro on human A549 lung epithelial cells exposed to 95% O2 for 24 hours, and in vivo by tracheal instillation or nebulization into the lungs of rats exposed intermittently or continuously to 90% O2 for a cumulative 72 hours. Our results showed that the preparation was enriched in collagen, reduced in glycosaminoglycans, and contained various bioactive molecules. Particle size was concentration-dependent. Compared to the respective controls treated with cell culture medium in vitro or saline in vivo, ECM inhalation normalized cell survival and alveolar morphology, and reduced hyperoxia-induced apoptosis and oxidative damage. This proof-of-concept study established the methodology, feasibility and therapeutic potential of exogenous solubilized ECM for pulmonary cytoprotection, possibly as an adjunct or potentiator of conventional therapy.